2022
DOI: 10.1186/s41687-022-00467-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental health impact on healthcare workers due to the COVID-19 pandemic: a U.S. cross-sectional survey study

Abstract: Background The COVID-19 pandemic has impacted the mental health and well-being of health care workers (HCWs). This study examined mental health outcomes and COVID-related stress impacts among a diverse sample of ambulatory HCWs, including clinicians and support staff, as well as the associations between mental health outcomes and work impairments in this population. Detailing these results can help in designing interventions to alleviate this burden. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 30 publications
3
17
0
2
Order By: Relevance
“…In terms of sociodemographic, work, and COVID-19-related characteristics, our findings showed that age, in a model with only control variables, was a significant negative predictor of anxiety and stress, which means that older healthcare workers reported less anxiety and stress. This finding is in line with the results of research conducted by Biber et al in the USA [ 44 ] and Yassin et al in Jordan [ 45 ]. Moreover, in the model with only control variables, gender was a significant predictor of mental health status indicators of anxiety and stress in the sense that women had higher levels of anxiety and stress, which is in line with the studies conducted by Xiao et al [ 26 ], Biber et al [ 44 ], and Lai et al [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…In terms of sociodemographic, work, and COVID-19-related characteristics, our findings showed that age, in a model with only control variables, was a significant negative predictor of anxiety and stress, which means that older healthcare workers reported less anxiety and stress. This finding is in line with the results of research conducted by Biber et al in the USA [ 44 ] and Yassin et al in Jordan [ 45 ]. Moreover, in the model with only control variables, gender was a significant predictor of mental health status indicators of anxiety and stress in the sense that women had higher levels of anxiety and stress, which is in line with the studies conducted by Xiao et al [ 26 ], Biber et al [ 44 ], and Lai et al [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Pandemic hits on healthcare system: The pandemic's longest and most deadly surge has posed risks to quality of care and left medical professionals exhausted. Various studies on health professionals show work-related stress, sleep disturbances and burnouts in 60% (Al-Otaibi et al, 2022;Biber et al, 2022;Koontalay et al, 2021); and hospitalization within 6 months of the pandemic starting 15% (Gholami et al, 2021). Also, WHO assumes that more than 1,15,000 health professionals may have died in the period between January 2020 and May 2021, and illnesses kept at least 500,000 health workers out of the US labor force alone (Guilford, 2022;WHO, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The pandemic's longest and most deadly surge has posed risks to quality of care and left medical professionals exhausted. Various studies on health professionals show workrelated stress, sleep disturbances and burnouts in 60% (Koontalay et al, 2021;Al-Otaibi et al, 2022;Biber et al, 2022); and hospitalization within 6 months of the pandemic starting 15% (Gholami et al, 2021). Also, WHO assumes that more than 1,15,000 health professionals may have died in the period between January 2020 and May 2021, and illnesses kept at least 500,000 health workers out of the US labor force alone (WHO, 2021;Guilford, 2022).…”
Section: (E) Pandemic Hits On Healthcare Systemmentioning
confidence: 99%